Cyberbullying among teenage K-pop fans - Andriani Andriani; Citra Rosalyn Anwar; Nur Fitriani Akram; Nur Aeni Alimuddin (Program Studi bimbingan Konseling PPs UNM Makassar, 2020)
This study aims to discuss how teenage K-pop fans need a proper approach to be introduced to the forms of cyberbullying, to describe how to recognize and overcome cyberbullying, and to discuss K-pop as media literacy for K-pop fans. This study was a library research with a qualitative approach. Data were collected through questionnaire and observation. The results of observation indicated that the easy access to the internet and the unlimited use of social media have contributed to the popularity of K-pop in Indonesia. K-pop fans can easily access their idols’ songs, music videos, activities, etc. Social media, which have been widely used thanks to the convenience and affordability of internet access, have posed positive and negative impacts. One of the most alarming negative impacts of social media is cyberbullying. The results of the study showed that: 1) there were different forms of cyberbullying experienced by K-pop fans, and 2) there were different sources of cyberbullying experienced by teenage K-pop fans, including inside, internal, and external sources.